2010
DOI: 10.1097/iop.0b013e3181d644cf
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Effectiveness of Antibiotic Prophylaxis in External Dacryocystorhinostomy: A Review of 697 Cases

Abstract: This study questions the generalized use of prophylactic antibiotics for external dacryocystorhinostomy, while providing evidence to indicate their use for patients who have had prior episodes of mucocele, mucopyocele, or acute dacryocystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…As an oral antibiotic, generally 3rd generation fluoroquinolons or extended-spectrum penicillin derivatives (cephalosporins, amoxicillin/clavulanic acid) are preferred. [15][16][17][18] In our study, all gram-positive isolates were susceptible to vancomycin, teicoplanin and linezolide. Besides, 96-100% of the microorganisms -excluding MRCNS-are susceptible to levofloxacin.…”
Section: Discussionsupporting
confidence: 46%
“…As an oral antibiotic, generally 3rd generation fluoroquinolons or extended-spectrum penicillin derivatives (cephalosporins, amoxicillin/clavulanic acid) are preferred. [15][16][17][18] In our study, all gram-positive isolates were susceptible to vancomycin, teicoplanin and linezolide. Besides, 96-100% of the microorganisms -excluding MRCNS-are susceptible to levofloxacin.…”
Section: Discussionsupporting
confidence: 46%
“…Dacryoadenitis frequently occurs in the newborn and in elderly women 25,26. In this study, there was 1 female infant (2 months old female) and nine of the ten patients were aged 60 years or older.…”
Section: Discussionmentioning
confidence: 71%
“…However, we defined conjunctival normalization time, which differs from the definitions for the same in the two above-mentioned studies (15,26) . Pinar-Sueiro et al reviewed the clinical records of 697 patients who had undergone EX-DCR and found S. aureus to be most sensitive to gentamicin, co-trimoxazole, rifampicin, clindamycin, vancomycin, tobramycin, mupirocin, cefuroxime-axetil, chloramphenicol, te tracycline, fusidic acid, and cefalotin (100% sensitivity to all), while penicillin demonstrated the worst activity against S. aureus with 83.3% resistance (27) . In a study by Pradeep et al (18) , antibiogram results demonstrated that Staphylococci represented the majority of cultured organisms (85%), and the most effective antibiotics against it were vancomycin, amikacin, third-generation cephalosporins, and amoxyclav (100%, 89%, 83%, and 78% sensitivity, respectively).…”
Section: Discussionmentioning
confidence: 99%